A Rare Cause of Shoulder Pain: Monostotic Fibrous Dysplasia - Bayram KELLE,; Aygül POLAT KELLE,; Kıvılcım EREN ERDOĞAN,; Erkan KOZANOĞLU, (Archives of Rheumatology, 2016)
Fibrous dysplasia is a rare bone disease which has a wide spectrum of symptoms depending on the involvement area such as pain, deformity, fracture, dyspnea or visual loss. One of the rare involvement areas is the bones around the shoulder. Fibrous dysplasia presents in two forms named monostotic or polyostotic. In this article, we present a case with monostotic fibrous dysplasia of the humeral head who admitted to our clinic with shoulder pain.